In the studio : visits with contemporary cartoonists - Hignite, Todd (Yale University Press, 2006)
Acknowledgments -- Introduction -- Robert Crumb -- Art Spiegelman -- Gary Panter -- Charles Burns -- Jaime Hernandez -- Daniel Clowes -- Seth -- Chris Ware -- Ivan Brunetti -- Selected bibliography -- Index